Manajemen UMKM dalam Menghadapi Covid-19 (Studi Kasus UMKM Susu Kedelai Plus “Man Jadda Wajada” Srandakan Bantul) - Ulistiyana Widi Subekti; Rarasati Mawftiq (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
The purpose of this study was to determine the marketing management of UMKM during Covid-19 and to determine the production management of UMKM during Covid-19 in Gunung Saren, Trimurti, Srandakan, Bantul, Yogyakarta. The research method of this study is a qualitative field research with a case study on UMKM Soy Milk Plus Man Jadda Wajada. The data collection techniques include primary data and secondary data, primary data includes observation, interviews, and documentation. While secondary data includes, collection of books, articles, journals, documentation files, and library materials related to study. The results of the study show that production management has several considerations such as (1) the decision process regarding the production process which regulates the packaging cover and other production facilities, (2) the community's decision capacity regarding production capacity before and after the pandemic, (3) inventory decisions regarding the amount of inventory in production process, (4) quality to pay attention to the quality of the products delivered to consumers, (5) human resources regarding how the community and UMKM get each other's attention and motivation and support. The marketing management has several stages, (1) the planning stage through a door to door strategy, traditional markets, to schools, children's posyandu, and so on, (2) the organizing stage grouping five employees divided into sections, namely in milling, screening, cooking, packaging, and marketing sections, (3) the stage of driving this process all activities are carried out, where the leader or chairman of UMKM has to mobilize all employees, and provide motivation, encouragement and an example in leading, and (4) stage supervision oversees an activity or work in accordance with their respective main tasks.